STATE POLICY TO SUPPORT SUSTAINABLE DEVELOPMENT OF TERRITORIAL COMMUNITIES IN UKRAINE - SHESTAKOVSKA Tetіana; DEMENTOV, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article comprehensively examines the state policy of supporting the sustainable development of territorial communities in the context of the transformation of the public administration system, strengthening the processes of decentralization and adaptation to the challenges of the war and post-war periods. The theoretical and methodological principles of the concept of "sustainable development" in the context of local self-government are determined, and the main approaches to the formation and implementation of the policy of sustainable development of territories are systematized. Particular attention is paid to the analysis of strategic documents of the state level, including the State Strategy for Regional Development for 2021–2027, the National Economic Strategy until 2030, as well as other sectoral policies that directly or indirectly affect the development of communities. In the process of the study, financial mechanisms for supporting communities were analyzed, in particular, the functioning of the system of inter-budgetary transfers, state subventions and subsidies, as well as the attraction of international technical assistance funds. It is substantiated that state policy should be not only reactive, but also proactive - one that contributes to the long-term self-sufficiency of communities, their economic sustainability, environmental balance and social cohesion. The role of local governments in the implementation of state policy is considered, the importance of strengthening human resources, digital transformation of management, and involving residents in making management decisions is emphasized. The article also emphasizes the need to improve mechanisms for monitoring and assessing the effectiveness of the implementation of sustainable development policies using indicators synchronized with the UN Sustainable Development Goals. The main barriers to the effective implementation of state policy to support communities are identified, including: imbalance in financial provision, fragmentation of the regulatory field, limited coordination between levels of government. As a result of the analysis, a number of practical recommendations were proposed to improve the state policy of supporting the sustainable development of territorial communities, in particular, the creation of stimulating financial instruments, strengthening the participation of communities in the programming of state and regional policies, expanding the functions of regional development agencies, institutionalizing monitoring of results based on clearly defined qualitative and quantitative indicators.